Correlation Analysis Between Factors Influencing NFC Mobile Wallet Proximity Payment and the Intention to Use - Mohammed Abdulllah Al-Amria, Redhwan; Maaropa, Nurazean; Narayana Samya, Ganthan; Azmeela Shariffa, Sya; Yahyaa, Yazriwati (International Journal of Engineering and Technology, 2018)
The rapid evolution of mobile technologies and increasing diffusion of smartphones have given opportunity for innovative companies to create new payment solutions and offer value-added services to their customers. Near Field Communication (NFC) mobile payment has been emerging as a noticeable phenomenon that can enable consumers to turn their smartphones into digital wallets. Although there has been a wide coverage on mass consumer acceptance of mobile payments, lack of effort made on the study related to acceptance of NFC mobile wallet proximity payment that considers both the human and security perspectives. The purpose of this study is to identify the factors influencing the secure use of NFC mobile payment system. The study proposed an acceptance model to help in mitigating the vulnerabilities of NFC technology thus builds understanding on how to improve the uptake rate of the technology. Aconceptual model was developed considering two main dimensions containing eight independent factors, which are: Perceived Ease of Use, Perceived Usefulness, Ubiquity, Awareness, Perceived Risk, Structural Assurance, Security and Privacy, and Trust. The study conducts a survey questionnaire that involves 209 valid respondents to evaluate the proposed conceptual technology acceptance model of NFC mobile wallet proximity payment system. The result of the analysis shows that all the independent variables (Perceived Ease of Use, Perceived Usefulness, Ubiquity, Awareness, Perceived Risk, Structural Assurance, Security and Privacy, and Trust) have significant influence to the acceptance of NFC Mobile Wallet Proximity Payment in Malaysian environment. All factors are found to have positive influence on the acceptance except for Perceived Risk entailing future works to be conducted qualitatively to obtain a more in-depth meaning of the result of this study.Â Â